Making sense of the social world methods of investigation - Chambliss, Daniel F.; Schutt, Russell K. (Los Angeles SAGE, 2019)
"Making Sense of the Social World, Sixth Edition is an engaging, accessible introduction to social research for students who need to understand methodologies and their results. It provides a balanced treatment of qualitative and quantitative methods, integrating substantive and compelling examples and research techniques throughout. It is written in a less formal style than many comparable texts, complete with practical examples drawn from everyday experience Features and Benefits: Brief and accessible treatment of the subject matter, appropriate for undergraduate or graduate level courses. This is a social research methods textbook which students actually like to read. Wide ranging examples with real data offer interesting, real-world applications to students makes the book more relevant than competitors texts. Full chapter on ethics as well as end-of-chapter sections to apply ethical considerations to the method under study coupled with ethics questions for discussion and review. Carefully developed coverage of all essential elements of social research methods including validity, causation, experimental and quasi-experimental design, and techniques of analysis - topics cited as most challenging for students. Excellent, wide-ranging end-of-chapter exercises sets."--
Includes bibliographical references (pages 387-397) and index.
Keywords: Social problems -- Research; Social sciences -- Research